2007
DOI: 10.1002/nav.20215
|View full text |Cite
|
Sign up to set email alerts
|

Exact expected values of variance estimators for simulation

Abstract: Abstract:We formulate exact expressions for the expected values of selected estimators of the variance parameter (that is, the sum of covariances at all lags) of a steady-state simulation output process. Given in terms of the autocovariance function of the process, these expressions are derived for variance estimators based on the simulation analysis methods of nonoverlapping batch means, overlapping batch means, and standardized time series. Comparing estimator performance in a first-order autoregressive proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…In addition, estimating the variance of the sample mean is also crucial in calculating confidence and prediction intervals of the population mean and the probability of selecting from alternatives correctly. Variance-estimation algorithms requiring (1) O memory storage without requiring the value of n a priori are needed when either the sample size is unknown a priori or the sample size is extremely large. The DNBM and DPBM estimators are the only two existing finite-memory algorithms for estimating the variance of the sample mean that do not require knowledge of the sample size a priori.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estimating the variance of the sample mean is also crucial in calculating confidence and prediction intervals of the population mean and the probability of selecting from alternatives correctly. Variance-estimation algorithms requiring (1) O memory storage without requiring the value of n a priori are needed when either the sample size is unknown a priori or the sample size is extremely large. The DNBM and DPBM estimators are the only two existing finite-memory algorithms for estimating the variance of the sample mean that do not require knowledge of the sample size a priori.…”
Section: Discussionmentioning
confidence: 99%
“…Proof of Theorem 1 Parts of this proof run parallel to Theorem 3 and the corresponding examples in Aktaran-Kalaycı et al (2007). We use the notation f j (t) = f cos, j (t).…”
Section: Appendixmentioning
confidence: 98%
“…ofAktaran-Kalaycı et al (2007) and the references cited therein. The effect of j with respect to the magnitude of the negative bias of A ( f cos, j ; 1, m) is apparent.…”
mentioning
confidence: 99%
“…This research paper addresses the first issue; the second issue was studied in [13]. Song and Schmeiser [12] showed that nvar(Y n) = 0 2 0 1 2 n + o(n 01 ) (1) where 0 = 1 + 2 1 h=1 h is the sum of all correlations and 1 = 2 1 h=1 h h is the sum of all weighted correlations. The lag-h correlation of Y i and Y i+h , h = corr(Y i ; Y i+h ), satisfies h = O( h ) for h = 1; 2; .…”
Section: Introductionmentioning
confidence: 99%
“…The lag-h correlation of Y i and Y i+h , h = corr(Y i ; Y i+h ), satisfies h = O( h ) for h = 1; 2; . .., with 2 (0; 1) to reflect a general correlation structure for a wide range of stochastic processes, including waiting times in a steady-state M/M/1 queueing system [1].…”
Section: Introductionmentioning
confidence: 99%